Trapping virus-loaded aerosols using granular material composed of protein nanofibrils and iron oxyhydroxides nanoparticles - Armanious, Antonius; Wang, Heyun; Alpert, Peter A.; Medaglia, Chiara; Peydayesh, Mohammad; Zwygart, Arnaud Charles-Antoine; Gübeli, Christian; Handschin, Stephan; Bolisetty, Sreenath; Ammann, Markus; Tapparel, Caroline; Stellacci, Francesco; et al. (Frontiers in Soft Matter, 2023)
The ongoing COVID-19 pandemic has revealed that developing effective therapeutics against viruses might be outpaced by emerging variants, waning immunity, vaccine skepticism/hesitancy, lack of resources, and the time needed to develop virus-specific therapeutics, emphasizing the importance of non-pharmaceutical interventions as the first line of defense against virus outbreaks and pandemics. However, fighting the spread of airborne viruses has proven extremely challenging, much more if this needs to be achieved on a global scale and in an environmentally-friendly manner. Here, we introduce an aerosol filter media made of granular material based on whey protein nanofibrils and iron oxyhydroxides nanoparticles. The material is environmentally-friendly, biodegradable, and composed mainly of a dairy industry byproduct. It features filtration efficiencies between 95.91% and 99.99% for both enveloped and non-enveloped viruses, including SARS-CoV-2, the influenza A virus strain H1N1, enterovirus 71, bacteriophage Φ6, and bacteriophage MS2. While the filtration efficiencies were relatively high, they came at the cost of high pressure drop (≈0.03 bar). We believe that the methods and results presented here will contribute to advancing our understanding of granular-based aerosol filters, hopefully helping the design of highly-efficient granular media with low-pressure drops.